Azolla microphylla Bioremoval as Countermeasures Alternative of Heavy Metals (Zn) In the Cultivation Media - Fahri Muhammad; Syafriadiman '; Niken Ayu Pamukas (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted from March until April 2015 at the Laboratory of Environmental Quality Cultivation of the Faculty of Fisheries and Marine Science University of Riau. The aim of this research to find out the ability of Azolla microphylla remove heavy metals (Zn) in reducing the content of heavy metals (Zn) in the cultivation media. The method used was experimental method and complete randomized design (CAD) with 1 factor 4 treatments and 3 replications.The results of this research that giving of Azolla microphylla with different density give effect to the decrease in heavy metals (Zn) in the cultivation media. The best density during research was 30 g Azolla microphylla/L of water could reduce Zn content in the cultivation media was 57,69%.Key words : Heavy Metals (Zn), Azolla microphylla, Bioremoval